Quercetin nanoparticle complex attenuated diabetic nephropathy via regulating the expression level of ICAM-1 on endothelium - Tong F (Dove Medical Press, 2017)
Fei Tong,1,2 Suhuan Liu,1 Bing Yan,1 Xuejun Li,1 Shiwei Ruan,3 Shuyu Yang1 1Department of Endocrinology and Diabetes, The First Affiliated Hospital, Xiamen University, Xiamen, 2Department of Pathology and Pathophysiology, Provincial Key Discipline of Pharmacology, Jiaxing University Medical College, Jiaxing, Zhejiang, 3Academy of Integrative Medicine, Fujian University of Traditional Chinese Medicine, Fuzhou, People’s Republic of China Abstract: The purpose of the study was to reveal the therapeutic effect of quercetin (QUE) nanoparticle complex on diabetic nephropathy (DN) by regulating the expression of intercellular adhesion molecular-1 (ICAM-1) on endothelium as compared to free QUE. QUE 10 mg/kg as a single abdominal subcutaneous injection daily for 8 weeks continuously in diabetic rats and 10 mg/kg QUE nanoparticle complex as a single abdominal subcutaneous injection every 5 days, continuously administered for 8 weeks to diabetic rats. Blood and left kidneys were collected; pathological change of kidney, renal function, oxidative stress level, blood glucose level, serum lipid, urine protein, and albumin/creatinine ratio were measured; and neutrophil adhesion, ICAM-1 expression, and CD11b+ cells infiltration were observed. Both QUE and QUE nanoparticle complex preconditioning ameliorated the pathological damage of kidney and improved renal function, alleviated renal oxidative stress injury, restricted inflammatory cells infiltration, and downregulated the ICAM-1 expression as compared to DN group, while QUE nanoparticle complex significantly alleviated this effect. Keywords: nanoparticle complex, quercetin, DN, ICAM-1, CD11b+, endothelium